2022
DOI: 10.3390/nu15010095
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Patterns and Their Gender Differences among Rheumatoid Arthritis Patients: A Descriptive Study

Abstract: Dietary factors probably play a role in the pathogenesis and clinical course of rheumatoid arthritis (RA). There is a paucity of specific dietary guidelines for RA patients and little information on their implementation in daily life. Therefore, this study aimed to determine the nutritional status and provision of nutritional education among outpatients with RA. Here, 61 patients were included with a sex ratio of 2.03 (f/m). Based on BMI, 22% of women were overweight and 32% obese, whereas 50% of men were over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 75 publications
0
3
0
Order By: Relevance
“…A 3-day estimated dietary record was collected from 61/61 patients and analyzed as previously described [ 42 ]. Dietary intake was quantified and analyzed by a nation-customized nutrition database (PRODI ® 6 expert, Nutri-Science GmbH, Freiburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…A 3-day estimated dietary record was collected from 61/61 patients and analyzed as previously described [ 42 ]. Dietary intake was quantified and analyzed by a nation-customized nutrition database (PRODI ® 6 expert, Nutri-Science GmbH, Freiburg, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…The clinical and demographic data of patients are presented in Table 1. The baseline anthropometric, metabolic, and nutrition data have been published previously [40,41]. Further patient data (history and medication) are presented in Table S3.…”
Section: Patient Characteristicsmentioning
confidence: 99%
“…In our study, we observed a difference in zonulin antibody expression between the normal and asthma groups in the bronchial epithelium from the lung tissues. It has been proposed that increased intestinal permeability is present in allergic diseases including bronchial asthma [12], and zonulin antibody staining has been conducted in the intestinal epithelium of patients with various disorders [14][15][16]. However, studies on zonulin antibody expression in the bronchial epithelium have been less extensive than those on the intestinal epithelium, and the relationship between zonulin and airway inflammation still requires further evaluation.…”
mentioning
confidence: 99%